The economic world view : (Cambridge University Pres, 2001)
These essays seek to unearth the "ontological underworld" that shapes the criteria economists use in making choices among theories to understand economic behavior. These criteria include fundamental, unarticulated ideas regarding the basic constitutents and structure of social reality, that is, about human beings and the social arrangement of their lives. This important collection will be of great value to economists and philosophers of social sciences.